Association of COL4A1 gene polymorphisms with cerebral palsy in a Chinese Han population. Issue 2 (9th February 2016) - Bi, D.; Wang, H.; Shang, Q.; Xu, Y.; Wang, F.; Chen, M.; Ma, C.; Sun, Y.; Zhao, X.; Gao, C.; Wang, L.; Zhu, C.; et al.
Abstract : The basement membrane (BM) is an extracellular matrix associated with overlying cells and is important for proper tissue development, stability, and physiology. COL4A1 is the most abundant component of type IV collagen in the BM, and COL4A1 variants can present with variable phenotypes that might be related to cerebral palsy (CP). We postulated, therefore, that variations in the COL4A1 gene might play an important role in the etiology of CP. In this study, six single nucleotide polymorphisms (SNPs) in the COL4A1 gene were genotyped among 351 CP patients and 220 healthy controls from the Chinese Han population. Significant association was found for an association between CP and rs1961495 (allele: p = 0.008, odds ratio (OR) = 1.387, 95% confidence interval (CI) = 1.088–1.767) and rs1411040 (allele: p = 0.009, OR = 1.746, 95% CI = 1.148–2.656) SNPs of the COL4A1 gene. Multifactor dimensionality reduction analysis suggested that these SNPs had interactive effects on the risk of CP. This study is the first attempt to investigate the contribution of polymorphisms in the COL4A1 gene to the susceptibility of CP in a Chinese Han population. This study shows an association of the COL4A1 gene with CP and suggests a potential role of COL4A1 in the pathogenesis of CP. Abstract :